"A volta dos que não foram": Quem são e o que veicularam em suas candidaturas os "parlamilitares" eleitos em em 2018? - Paglis Marques Plácido, Caio; Gallo, Carlos Artur (Brasiliana: Journal for Brazilian Studies, 2022)
The present paper has as its central theme the profile and contents or parliamentarians election contents by members of the brazilian Armed Forces and Public Security Agencies elected in 2018. During the 2018 election process, it was possible to identify, at least, 26 congressmen who linked their patents to their nominations and ballot names. After data collection, it was possible to draw a profile of these 26 congressmen regarding the party, gender, ethnicity, occupation and other relevant characteristics. It was also possible to identify, by analyzing the posts on the social networks Facebook and YouTube of these parliamentarians of the electoral period, two types of content instrumentalized in the campaigns - the programmatic content and ideological content. The analysis made it possible to contribute to the debate of the “new” right in the Political Science and to conclude that these candidatures are related to the legacies of authoritarianism in Brazil.